Systemic lupus erythematosus or lupus-like syndrome in patients with HIV infection: clinical case review - Margarita A. Gromova (LLC "MEDIAFORMAT", 2021)
Background. Due to multi-organ lesions and a wide range of clinical manifestations, human immunodeficiency virus (HIV infection) resembles systemic connective tissue diseases, particularly systemic lupus erythematosus (SLE). Similarity of immune disorders in patients with HIV infection and SLE may lead to misdiagnosis resulting in wrong tactics of treatment (prescribing immunosuppressive therapy instead of high-dose antiretroviral therapy). Aim. To report the HIV infection and SLE differential diagnosis challenges. Results. By January 2021, the analysis of national literature revealed two cases of HIV infection in young women, initially misdiagnosed with suspected SLE. In addition to two patients described in literature, one more female patient with SLE manifestations combined with advanced stage of HIV infection was examined. Conclusion. HIV and SLE differential diagnosis is the ultimate challenge for clinicians. Physicians should be especially apprehensive about HIV infection when making the diagnosis of SLE. SLE therapy in patients with HIV infection should be appointed according to strict indications.